Education and economic performance in the OECD countries: an elusive relationship? - Martin, John P. (Statistical and Social Inquiry Society of Ireland, 1998)
One of the most common political mantras to-day is that education is the handmaiden of economic growth and prosperity. Politicians like Bill Clinton and Tony Blair constantly trumpet the need to invest in education and training of the work force, and improve the quality of that investment, in order to compete effectively in to-day?s increasingly globalised and knowledge-intensive world economy. Population ageing which is set to hit many OECD and non-OECD economies over the next few decades will also increase the pressure on individuals and firms to invest more in upgrading their skills and competences in order to maintain productivity growth and living standards in the future. Thus, investment in education and training, so-called ?human capital accumulation?, is once again the political flavour of the month.
Symposium on the economic returns to education
Read before the Society, 19 February 1998
Keywords: Education; Human capital; Economic growth; 314.15